-(3y+2)-(-2y-6)=0

Simple and best practice solution for -(3y+2)-(-2y-6)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(3y+2)-(-2y-6)=0 equation:


Simplifying
-1(3y + 2) + -1(-2y + -6) = 0

Reorder the terms:
-1(2 + 3y) + -1(-2y + -6) = 0
(2 * -1 + 3y * -1) + -1(-2y + -6) = 0
(-2 + -3y) + -1(-2y + -6) = 0

Reorder the terms:
-2 + -3y + -1(-6 + -2y) = 0
-2 + -3y + (-6 * -1 + -2y * -1) = 0
-2 + -3y + (6 + 2y) = 0

Reorder the terms:
-2 + 6 + -3y + 2y = 0

Combine like terms: -2 + 6 = 4
4 + -3y + 2y = 0

Combine like terms: -3y + 2y = -1y
4 + -1y = 0

Solving
4 + -1y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + -1y = 0 + -4

Combine like terms: 4 + -4 = 0
0 + -1y = 0 + -4
-1y = 0 + -4

Combine like terms: 0 + -4 = -4
-1y = -4

Divide each side by '-1'.
y = 4

Simplifying
y = 4

See similar equations:

| 8(2+v)+33v=11v | | 8+3t-5=8t+8-4t | | 2k+4=8 | | 6n+3=39 | | -2n=10 | | 4-35(3a+4)=7 | | (n-4)*8=32 | | (n+4)*2=12 | | n-2=-7 | | 3x-36= | | 1=0.5(6y+2) | | -130=10(-9+x) | | y+7=-4 | | X+(3x+3)=19 | | y+7=-24 | | 35x^2y^4z^8-56x^4y^7z^10= | | -3(m-8)=36 | | -3v=30 | | .25n+.1=9.8 | | -8n=-24 | | 42x^2y^3-35x^3y^4-14x^5y^6= | | 3x-10-x=2x-4 | | 5x+4=35 | | .3(m+1.5)=1.5(2m+3) | | 4x+5=35 | | 7x^5+70x^3+12x^2= | | x/3+2=12 | | 5/8+7/8= | | 3/7+4/7= | | M^2+8m-65=0 | | -x/3=8 | | 8-5lnx=6 |

Equations solver categories